Contribuições de Bakhtin para os sistemas de RPG modernos - Santana, Maria Eduarda da Matta (Universidade Federal de São Carlos, 2025)
In this final term paper, analyses the influence of Dungeons & Dragons in three authorial RPGs (homebrews), investigating the presence of dialogic relations, and echoes, of the officialized system even in games that are not directly inspired by it. The research compares mechanics, narratives and structures of the three systems studied, highlighting similarities and differences both between them and in relation to the D&D macrocosm. Based on Mikhail Bakhtin’s concepts of polyphony and dialogism, the study seeks to demonstrate how RPGs are built from multiple voices in constant interaction. In the end, it is concluded that the creation of new systems follows a dialogic logic, evidencing the continuous influence of D&D on the structure and evolution of authorial RPGs.
Bakhtin's contribuitions to modern RPG systems
Keywords: RPG; D&D; Bakhtin; Vozes; Linguística; Voices; Echoes; Linguistics; LINGUISTICA, LETRAS E ARTES